Analysis of Readiness for ISO 17025 Implementation in Laboratories in Indonesia (Case Study: iRATco Laboratory Services Bogor) - Merdiwijaya, Bagus; Sarma, Ma'mun; Hidayatulloh, Furqon Syarief (Dinasti Publisher, 2025)
This study aims to assess the readiness of iRATco Veterinary Laboratory Services Bogor in implementing the ISO 17025 standard. Using a descriptive approach and the Analytical Hierarchy Process (AHP) method, the research reveals that the laboratory’s readiness is at a fairly good level, viewed from three main dimensions: individual, group, and organizational structure. Commitment is identified as the most influential determinant of implementation readiness, followed by competence, supervision, evaluation, consistency, and communication. Overall, employees’ perception of ISO 17025 implementation is positive; however, improvements are still needed, particularly in the consistency of procedure execution and the effectiveness of internal communication. The validity and reliability tests of the research instrument also confirmed that the measurement tool used was appropriate for assessing organizational readiness. Thus, iRATco has significant potential to implement ISO 17025 effectively, provided that managerial and technical aspects are strengthened comprehensively and sustainably. The success of ISO 17025 implementation in this laboratory largely depends on the synergy between leadership commitment, human resource readiness, and the support of a well-structured and well-documented quality management system.